Health and Wealth of Elderly Couples : Causality Tests Using Dynamic Panel Data Models - Pierre-Carl Michaud; Arthur van Soest (Institute for the Study of Labor (IZA), 2004)
A positive relationship between socio-economic status (SES) and health, the so-called "health-wealth gradient", is repeatedly found in most industrialized countries with similar levels of health care technology and economic welfare. This study analyzes causality from health to wealth (health causation) and from wealth to health (wealth or social causation) for elderly couples in the US. Using six biennial waves of couples aged 51-61 in 1992 from the Health and Retirement Study, we compare the recently developed strategy using Granger causality tests of Adams et al. (2003, Journal of Econometrics) with tests for causality in dynamic panel data models incorporating unobserved heterogeneity. While Adams et al. tests reject the hypothesis of no causality from wealth to husband's or wife's health, the tests in the dynamic panel data model do not provide evidence of wealth-health causality. On the other hand, both methodologies lead to strong evidence of causal effects from both spouses' health on household wealth.
Keywords: D31; J14; I12; C33; 330; health; inequality; aging; dynamic panel data models; causality; Sozialer Indikator; Gesundheit; Einkommensverteilung; Alte Menschen; Kausalanalyse; Panel; Statistischer Test; Schätzung; Vereinigte Staaten